ANALISIS PENGUKURAN KECEPATAN REAKSI START PADA LARI 50 METER PADA ATLET PASI KAMPAR - M. Nurul Aqli; Yusrina, Etika; Putra, Arbi Dwi; Zikri, Aditya; Tetikay, Robert (Pusat Pengembangan Olahraga Universitas Pahlawan, 2025)
The purpose of this study is to find out the 50 Meter Sprint Running Speed in PASI Kampar athletes. The research method used is a non-experimental method in the form of observational. The sample of this study was taken as many as 12 people to determine the sample using the purposive sampling technique, which is deliberate sampling, that is, the researcher determined the sample to be taken as many as 12 PASI Kampar athletes. The measurement of each sample is by conducting a 50-meter sprint running test. From the results of the calculation, Lcount (L0) was obtained as 0.140 and 0.140 and Ltable 0.161. Thus, it can be concluded that there is a significant relationship between the relationship between the explosive power of the leg muscles and the speed of running a 50-meter sprint in PASI Kampar athletes.